Prediction of Non-Cavitating Marine Propeller Noise - Satyavarma, K.L.; Devi, C. Neelima (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Noise reduction and control is an important problem in the performance of underwater acoustic systems. As the propeller rotates, it is subjected to unsteady force, which leads to discrete tonal noise, and cavitation. Therefore, underwater propeller noise can be classified into cavitating and non-cavitating noise Furthermore, sound generated by a propeller is critical in underwater detection and it is often related to the survivability of the vessel. This paper presents a numerical study on noises of the underwater propeller for different performance conditions. The non-Cavitating noise generated by an underwater propeller is analyzed numerically in this study. The flow field is analyzed with finite volume method (FVM), and then the acoustic analysis is made by the use of Ffowcs Williams–Hawkings (FW-H) formulation to predict the far-field acoustics at different operating conditions. Noise characteristics are presented according to different positions of hydrophones and speeds of the propeller. Computed results are shown to be in good agreement with experimental results.